More development - more migration? The "migration hump" and its significance for development policy co-operation with sub-Saharan Africa - Steffen Angenendt; Charles Martin-Shields; Benjamin Schraven (Stiftung Wissenschaft und Politik (SWP), 2017)
German and European efforts to reduce irregular migration, particularly from sub-Saharan Africa, place a great emphasis on development co-operation. The aim is for this to eliminate as many causes of such migration as possible. This raises questions concerning the interrelation of development and migration. In the academic debate, it is well established that socio-economic development promotes migration rather than reducing it. But this causal relationship is not as clear-cut as the corresponding 'migration hump' model suggests. It is evident that migration decisions are also influenced by further factors. It is therefore problematic when policy makers use this apparent evidence to assume stopping development aid will stop migration. The context of migration and development needs to be analysed with an eye towards managing multiple drivers of migration. Donor countries should also utilize development policy approaches that lead to co-operation with African partner states.
Keywords: 320